2010
DOI: 10.1094/phyto-100-1-0085
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Sugar, d-Allose, Confers Resistance to Rice Bacterial Blight with Upregulation of Defense-Related Genes in Oryza sativa

Abstract: We investigated responses of rice plant to three rare sugars, d-altrose, d-sorbose, and d-allose, due to establishment of mass production methods for these rare sugars. Root growth and shoot growth were significantly inhibited by d-allose but not by the other rare sugars. A large-scale gene expression analysis using a rice microarray revealed that d-allose treatment causes a high upregulation of many defense-related, pathogenesis-related (PR) protein genes in rice. The PR protein genes were not upregulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
67
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 42 publications
5
67
0
Order By: Relevance
“…In animal studies, detection of immunosuppressive activity in liver transplantation (Hossain et al 2000), a protective effect on liver ischemia reperfusion injury (Hossain et al 2003(Hossain et al , 2006, an inhibitory effect on reactive oxygen species (ROS) production (Murata et al 2003;Hirooka et al 2006), and anticancer activity on different cancer cell lines (Sui et al 2005a, b;Yamaguchi et al 2008;Hirata et al 2009) have been reported. Inhibition of root growth by D-psicose via the hexokinase-independent pathway (Kato-Noguchi et al 2005) and induction of resistance to bacterial blight disease in rice (Kano et al 2010) have been reported for plants. Thus, multiple pieces of evidence obtained from the different studies indicate that some rare sugars can effect living organisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal studies, detection of immunosuppressive activity in liver transplantation (Hossain et al 2000), a protective effect on liver ischemia reperfusion injury (Hossain et al 2003(Hossain et al , 2006, an inhibitory effect on reactive oxygen species (ROS) production (Murata et al 2003;Hirooka et al 2006), and anticancer activity on different cancer cell lines (Sui et al 2005a, b;Yamaguchi et al 2008;Hirata et al 2009) have been reported. Inhibition of root growth by D-psicose via the hexokinase-independent pathway (Kato-Noguchi et al 2005) and induction of resistance to bacterial blight disease in rice (Kano et al 2010) have been reported for plants. Thus, multiple pieces of evidence obtained from the different studies indicate that some rare sugars can effect living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the glucose epimer, D-allose, has an inhibitory effect on rice growth (Kano et al 2010). A large scale gene expression analysis using a microarray revealed that D-allose treatment changes the expression of many genes, including defense-related genes, in rice and that D-allose treatment of rice plants confers resistance to bacterial blight pathogen in rice (Kano et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Recently, Akimitsu's group, a pioneer in rare sugar research, through the use of powerful genetics study has shown that the rare sugar D-allose suppresses GA signaling pathway in rice.…”
mentioning
confidence: 99%
“…19,20 D-allose was found to inhibit the rice growth and prevent bacterial blight disease in rice as well. 21 Recently, Akimitsu's group, a pioneer in rare sugar research, through the use of powerful genetics study has shown that the rare sugar D-allose suppresses GA signaling pathway in rice. 22 D-allose strongly inhibited GA mediated α-amylase induction in embryo-less rice half seeds, 22 implicating a negative role of D-allose in the GA pathway.…”
mentioning
confidence: 99%